Pengaruh Penerapan Model Cooperative Integrated Reading and Composition Terhadap Hasil Belajar Siswa dalam Pembelajaran Tematik Kelas V SD Negeri 39 Pontianak Kota - Silvia Arum Tri Marlinda; Hamdani Hamdani; Siti Halidjah (Journal on Education, 2023)
This study aims to analyze the effect of applying the Cooperative Integrated Reading and Composition model to student learning outcomes in the thematic learning of class V at SD Negeri 39 Pontianak Kota. The research method used was an experimental design with a pre-experimental design and a non-equivalent control group design. The population of all fifth-grade students totaled 56 students. The research sample was VA class students as an experimental class totaling 28 students and VB class as a control class totaling 28 students. The data collection technique was a measurement technique, and the data collection tool was a written test using multiple choice. Data analysis obtained the average post-test results for the experimental class (71.285) and the average post-test for the control class (64.5). The results of the hypothesis test using the t-test (Polled Variance) obtained t-count = (2.07) while for dk (28+28-2=54) with α = 5% received t-table = (1.874), which means t-count> t-table, then Ha is accepted, this proves that there is an effect of applying the Cooperative Integrated Reading and Composition model in thematic learning. Based on the effect size (ES) calculation results, ES = 0.557, included in the medium criteria. Thus, it concluded that applying the Cooperative Integrated Reading and Composition model in thematic learning positively influences the learning outcomes of class V students at SD Negeri 39 Pontianak Kota.